Sedimentation of the Cretaceous Bauru Group in São Paulo, Parana Basin, Brazil - de Paula e Silva, Flavio [UNESP]; Kiang, Chang Hung [UNESP]; Caetano Chang, Maria Rita [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
The post-basaltic sediments of the Cretaceous Bauru Group in the Parana Basin cover an area of 117,000 km(2) in São Paulo State, and are subdivided into the Caiua, Pirapozinho, Santo Anastacio, Birigui, Aracatuba, Adamantina and Marilia formations. The sedimentation of Bauru Group was controlled by a combination of post-basaltic tectonism (responsible for the migration of the depocenters), erosion and climatic changes. Three main depositional phases are separated by two erosive/non-depositional phases defining depositional sequences. The fluvial-lacustrine deposition represented by the Caiua/Pirapozinho formations (first sequence), initially filled the basaltic substratum troughs. After an erosional interval, the Santo Anastacio Formation was deposited and overlapped (eastward) underlying beds (second sequence). Renewed erosion and tectonism initiated the last depositional sequence, with the migration of the depocenter to the Queiroz depression. High topographic gradients initially favored the accumulation of fluvial deposits of braided systems of the Birigui Formation. With the enlarging of the depositional area, a lacustrine system was formed (Aracatuba Formation) and overlapped by a fluvial system with progradation of lacustrine deltas (Adamantina Formation). The sedimentation of the Bauru Group ceased with deposition of marginal fans of Marilia Formation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bauru Group; Sedimentation; Depositional system; Stratigraphy